Guidance on Understanding Short- and Long-Term Securities Investments and Simulation of Their Recording as an Alternative for Business Fund Management at Archive Studio MSME - Wahyuni; Nurul Fuada; Dwi Azzahrah Syarif; Hesti Marwah; Muh. Asri Syamjun S; Muh Al Amin Bintang Saputra (www.amertainstitute.com, 2026)
Micro, small, and medium enterprises (MSMEs) frequently encounter challenges in financial recordkeeping and cash management, limiting their ability to make informed financial decisions and sustain business growth. While previous community engagement programs have primarily focused on introducing simple bookkeeping based on the Indonesian Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), limited attention has been given to integrating financial reporting with investment management strategies. This community service project aimed to enhance financial literacy by providing assistance in preparing simple financial statements and introducing short- and long-term securities investments as alternative approaches to managing surplus business funds. The program was implemented at Archive Studio, a clothing retail MSME in Makassar, Indonesia, using a participatory assistance approach involving observation, interviews, financial transaction analysis, mentoring sessions, and accounting simulations. The activities resulted in the preparation of complete financial statements, including journals, ledgers, income statements, statements of changes in equity, and statements of financial position. In addition, participants gained practical understanding of the accounting treatment for short- and long-term securities investments through transaction simulations. The mentoring process also improved the participant's ability to distinguish between business assets, operating expenses, and owner withdrawals, thereby supporting more transparent financial management. The novelty of this program lies in integrating SAK EMKM-based financial reporting with securities investment accounting simulations, providing MSMEs with a comprehensive framework for both financial reporting and strategic fund allocation. This integrated approach contributes to strengthening financial literacy and offers a practical model for improving MSME financial sustainability and decision-making.